2015
DOI: 10.9738/intsurg-d-14-00234.1
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of COX-2 and iNOS in Angiogenesis of Superficial Esophageal Squamous Cell Carcinoma

Abstract: Using immunohistochemical staining, the present study was conducted to examine whether cyclooxygenase (COX)-2 and inducible nitric oxide synthase (iNOS) affect angiogenesis in early-stage esophageal squamous cell carcinoma (ESCC). We also analyzed the correlation between these two factors. Cyclooxygenase 2, iNOS, and angiogenesis in early-stage ESCC are unclear. Using 10 samples of normal squamous epithelium, 7 samples of low-grade intraepithelial neoplasia (LGIN), and 45 samples of superficial esophageal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…In addition to NO, prostaglandin E2 (PGE 2) released from immune cells plays a major role in a variety of inflammatory responses catalyzed by the expression of COX-2 [44]. NO produced by iNOS in the inflammatory response contributes to upregulation of COX-2 via crosstalk between NO, COX-2, and PGE2 [45]. However, PLE did not inhibit the expression COX-2 or prostaglandin E2 in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition to NO, prostaglandin E2 (PGE 2) released from immune cells plays a major role in a variety of inflammatory responses catalyzed by the expression of COX-2 [44]. NO produced by iNOS in the inflammatory response contributes to upregulation of COX-2 via crosstalk between NO, COX-2, and PGE2 [45]. However, PLE did not inhibit the expression COX-2 or prostaglandin E2 in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…COX-1 is constitutively expressed in most tissues, while COX-2 is the inducible isoform, which is responsible for the elevated production of PGs in response to various inflammatory stimuli, hormones, and growth factors [ 4 ]. Accumulating evidence has demonstrated that COX-2 plays an important role both in tumor development and progression [ 5 10 ], including ESCC [ 11 – 16 ]. Epidemiological studies have indicated that the regular use of aspirin can reduce the risk of esophageal cancer by up to 90% [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have indicated that the regular use of aspirin can reduce the risk of esophageal cancer by up to 90% [ 17 19 ]. We and others have shown that (1) COX-2 expression is a frequent phenomenon in human ESCC tissue samples and that positive expression is related to lymphatic metastasis [ 11 – 16 ]; (2) COX-2 inhibitors inhibit cell proliferation and induce apoptosis by inducing G0 / G1 cell-cycle arrest and down-regulating Bcl-2 expression [ 20 , 21 ] and the inhibition of COX-2 leads to tumor reduction in vivo [ 22 ]; and (3) a COX-2 inhibitor can inhibit migration and invasion of ESCC cells [ 23 ] These findings thus provide compelling evidence that COX-2 is an obligatory player in ESCC and that blocking COX-2 is an important therapeutic targets of ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…These angiogenic factors have been implicated in angiogenesis, vessel invasion, distant metastasis, and prognosis. We have previously calculated and reported the cyclooxygenase (COX)-2 and iNOS scores in early stage ESCC [30]. The expression of both COX-2 and iNOS by host cells was also strongly upregulated in M1 and M2 cancer and significantly correlated with MVD.…”
Section: Discussionmentioning
confidence: 95%
“…This is one limitation of the present study, and further investigation of this issue seems warranted. ESCC cells are also reported to express various angiogenic factors [7,8,12,19,[26][27][28][29][30] in the early stage of cancer progression. These angiogenic factors have been implicated in angiogenesis, vessel invasion, distant metastasis, and prognosis.…”
Section: Discussionmentioning
confidence: 97%